2021
DOI: 10.1021/acsnano.1c04660
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Band-Edge Potentials and Charge Storage in Colloidal Tin-Doped Indium Oxide (ITO) Nanocrystals

Abstract: Degenerately doped metal-oxide nanocrystals (NCs) show localized surface plasmon resonances (LSPRs) that are tunable via their tunable excess charge-carrier densities. Modulation of excess charge carriers has also been used to control magnetism in colloidal doped metal-oxide NCs. The addition of excess delocalized conduction-band (CB) electrons can be achieved through aliovalent doping or by postsynthetic techniques such as electrochemistry or photodoping. Here, we examine the influence of charge-compensating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 44 publications
7
26
0
Order By: Relevance
“…33,47 However, <n max > in undoped ZnO NCs was found to be on the order of 10 20 cm −3 , which is an order of magnitude smaller than that for doped In 2 O 3 NCs, where aliovalent doping is expected to increase the electron density. 13,17,45 Very similar trends in electron density are obtained with size series of Sn:In 2 O 3 NCs with different Sn atom % (Figure S18). Analogous to the results of the size series, for the doping series, volumetric addition of CoCp* 2 leads to an increase in the electron density and a simultaneous increase in the volume fraction of the plasmonic core (Figure S19).…”
Section: ■ Results and Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…33,47 However, <n max > in undoped ZnO NCs was found to be on the order of 10 20 cm −3 , which is an order of magnitude smaller than that for doped In 2 O 3 NCs, where aliovalent doping is expected to increase the electron density. 13,17,45 Very similar trends in electron density are obtained with size series of Sn:In 2 O 3 NCs with different Sn atom % (Figure S18). Analogous to the results of the size series, for the doping series, volumetric addition of CoCp* 2 leads to an increase in the electron density and a simultaneous increase in the volume fraction of the plasmonic core (Figure S19).…”
Section: ■ Results and Discussionsupporting
confidence: 72%
“…Photodoping studies on a doping series of Sn:In 2 O 3 NCs and other doped metal oxides have reported similar observations. 17,32,33,35,45 Here, we confirm and interpret these trends by analyzing the distribution of electrons between the core and depletion layer as chemical doping proceeds.…”
Section: ■ Results and Discussionsupporting
confidence: 58%
See 3 more Smart Citations